Antimicrobial therapy in complicated rhinosinusitis - Beatrice, Simion-Antonie Catrinel; Luiza, Bejenaru Paula; Bogdan, Popescu; Simona, Berteșteanu Gloria; Mihnea, Condeescu-Cojocărița; Ionela, Cîrstea Anca; Elena, Diaconu Teodora; Petra, Taher Bianca; Simona-Andreea, Rujan; Doinița, Oașă Irina; Gabriel, Berteșteanu Șerban Vifor; Raluca, Grigore (Frontiers in Microbiology, 2022)
Introduction Complicated rhinosinusitis is a rare but life-threatening pathology that requires both medical and surgical treatment as soon as possible. The spread of the infection from the paranasal sinuses affects, most often, the orbit, patients presenting diplopia, preseptal cellulitis, orbital cellulitis, or even blindness alongside exteriorization of puss from the middle meatus and nasal obstruction. Materials and methods We carried out a retrospective review of 32 patients that were diagnosed in our clinic with complicated rhinosinusitis from 2015 to 2022. All the patients received at least one intravenous antibiotic, and some also received antifungal drugs. All patients underwent surgery, either endoscopically or combined approach. Nasal washout or nasal swabs during surgery were sent for laboratory examination in all patients, and we studied the microbial etiology in these extensive infections. A database with all the information regarding demographic and medical data was established. Results 78% of the patients were male, with a mean age of 50.55. A wide range of antibiotics were used, while some patients, diagnosed with mucormycosis also received antifungal drugs. The mean hospitalization period was 12 days. We correlated the type of antibiotic with the hospitalization period and the outcome but also the degree of involvement of the orbit and the microbial strains identified. Discussion The management of patients with complicated rhinosinusitis is complex and dynamic and it must be tailored to every patient, after an interdisciplinary meeting with the infectious disease specialist, ophthalmologist, and rhinologist. The microbial strains that produce such important infections are sometimes multi-resistant or combined, patients usually already had followed a course of antibiotics at home, and choosing the right treatment is sometimes challenging.